Effects of pedal speed and crank length on pedaling mechanics during submaximal cycling - Barratt, P. R.; Martin, J. C.; Elmer, S. J.; Korff, T. (Medicine & Science in Sports & Exercise, 2016)
During submaximal cycling, the neuromuscular system has the freedom to select different intermuscular coordination strategies. From both a basic science and an applied perspective, it is important to understand how the central nervous system adjusts pedaling mechanics in response to changes in pedaling conditions. Purpose: To determine the effect of changes in pedal speed (a marker of muscle shortening velocity) and crank length (a marker of muscle length) on pedaling mechanics during submaximal cycling. Methods: Fifteen trained cyclists performed submaximal isokinetic cycling trials (90 rpm, 240 W) using pedal speeds of 1.41 to 1.61 m/s and crank lengths of 150 to 190 mm. Joint powers were calculated using inverse dynamics. Results: Increases in pedal speed and crank length caused large increases knee and hip angular excursions and velocities (P G 0.05), whereas ankle angular kinematics stayed relatively constant (P 9 0.05). Joint moments and joint powers were less affected by changes in the independent variables, but some interesting effects and trends were observed. Most noteworthy, knee extension moments and powers tended to decrease, whereas hip extension power tended to increase with an increase in crank length. Conclusions: The distribution of joint moments and powers is largely maintained across a range of pedaling conditions. The crank length induced differences in knee extension moments, and powers may represent a trade-off between the central nervous system's attempts to simultaneously minimize muscle metabolic and mechanical stresses. These results increase our understanding of the neural and mechanical mechanisms underlying multi-joint task performance, and they have practical relevance to coaches, athletes, and clinicians.